My little pony : friendship is magic. Princess Twilight Sparkle [videorecording (DVD)] (Shout! Factory, 2013)
Twilight Sparkle, one of the unicorn ponies in My Little Pony Friendship is Magic. After moving from Canterlot to Ponyville, so she can continue to study friendship under Princess Celestia's guidance, and regularly maintains correspondence with the Princess. She lives in the Golden Oaks Library along with her assistant Spike and her pet owl Owlowiscious. Later in the second season, her older brother, Shining Armor, marries her former foalsitter Princess Cadance, who inducts her into royalty.